2020
DOI: 10.1016/j.jcp.2019.109056
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamics of PDE systems with physics-constrained deep auto-regressive networks

Abstract: In recent years, deep learning has proven to be a viable methodology for surrogate modeling and uncertainty quantification for a vast number of physical systems. However, in their traditional form, such models require a large amount of training data. This is of particular importance for various engineering and scientific applications where data may be extremely expensive to obtain. To overcome this shortcoming, physics-constrained deep learning provides a promising methodology as it only utilizes the governing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
141
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(141 citation statements)
references
References 63 publications
0
141
0
Order By: Relevance
“…Coming to our rescue is the physics informed/constrained neural networks (PINN). Over the past two years, a number of studies on PINN can be found in the literature [1][2][3][4][5][6]. In these methods, the neural networks are trained to solve supervised learning problems while respecting any given law of physics described by general non-linear partial differential equations.…”
mentioning
confidence: 99%
“…Coming to our rescue is the physics informed/constrained neural networks (PINN). Over the past two years, a number of studies on PINN can be found in the literature [1][2][3][4][5][6]. In these methods, the neural networks are trained to solve supervised learning problems while respecting any given law of physics described by general non-linear partial differential equations.…”
mentioning
confidence: 99%
“…, x N . In our past work [9], we formulated a deep convolutional auto-regressive model for modeling the evolution of a transient PDE as a Markov chain. To increase the predictive capability of our model and integrate the low-fidelity observations, in this work we will use a deep recurrent neural network (RNN) formulation which is a standard approach for time-series predictions in deep learning [13].…”
Section: Transient Multi-fidelity Glowmentioning
confidence: 99%
“…Examples of the encoding and dense blocks are illustrated in Fig. 9 which have been used successfully for modeling many physical systems in the past [9,41,75,76]. The encoding blocks down-scale the feature maps forcing the model to learn low-dimensional representations while the densely connected blocks increase predictive accuracy of the model and have better performance than standard residual connections [22].…”
Section: Low-fidelity Conditioningmentioning
confidence: 99%
See 2 more Smart Citations